Simplified tai chi for beginners [videorecording (DVD)] : learn the 48 form : 10 minute routine - Silver, David; Yang, Chenhan (YMAA Publication Center, 2016)
The tai chi 48 form takes only 10 minutes to practice but offers benefits for your entire life.